Characterisation of ODS Fe-14Cr-2W-0.3Ti before and after high temperature triple and low temperature single ion irradiations - Scepanovic, M; Leguey, T; Auger, M; Lozano-Perez, S; Armstrong, D; Garcia-Cortes, I; de Castro, V (Elsevier, 2017)
Oxide dispersion strengthened reduced activation ferritic steels are being considered as structural materials for future fusion reactors and Gen IV fission reactors. In this work, the stability of the nanometric oxides after being irradiated at different conditions and temperatures has been investigated. A Fe-14Cr-2W-0.3Ti-0.3Y2O3 alloy was simultaneously triple-beam irradiated at 600°C with Fe, He and H ions. The same alloy was irradiated with Fe ions at -80°C. The microstructure of this alloy was investigated using Transmission Electron Microscopy, Atom Probe Tomography and nanoindentation before and after the irradiations. There were no significant changes in the morphology and chemical composition of the nanoparticles after the irradiations, although the size of the smaller ones tends to decrease for both irradiation conditions. Small irradiation-induced bubbles were present after the triple simultaneous irradiation at high temperature. Nanoindentation also shows no significant differences with a slight increase in hardness for the sample irradiated at low temperature, while softening appears in the high temperature irradiation.